Open wound : the long view of race in America - Evans, William McKee (University of Illinois Press, 2009)
In this boldly interpretive narrative, William McKee Evans tells the story of America's paradox of democracy entangled with a centuries-old system of racial oppression. This racial system of interacting practices and ideas first justified black slavery, then, after the Civil War, other forms of coerced black labor, and, today, black poverty and unemployment. At three historical moments, a crisis in the larger society opened political space for idealists to challenge the racial system: during the American Revolution, then during the "irrepressible conflict" ending in the Civil War, and, finally, during the Cold War and the colonial liberation movements. Each challenge resulted in a historic advance. But none swept clean. Many African Americans remain segregated in jobless ghettoes with dilapidated schools and dismal prospects in an increasingly polarized class society. Evans sees a new crisis looming in a convergence of environmental disaster, endless wars, and economic collapse, which may again open space for a challenge to the racial system. African Americans, with their memory of their centuries-old struggle against oppressors, appear uniquely placed to play a central role